Does the 2024 Indonesian President Elections Have an Impact to JII Companies Performance? - Kharista, Salwa Dina; Berakon, Izra (Islamic Economics Methodology, 2025)
This study aims to analyze the reaction of the Indonesian capital market, especially the Jakarta Islamic Index (JII) company, to three events in the 2024 Presidential Election (Pilpres): Determination of Presidential and Vice Presidential Candidates, Announcement of Winners by the KPU, and Inauguration of the President and Vice President. The event study method was used to test the influence of Abnormal Return (AR) and Trading Volume Activity (TVA) as indicators of market reaction. The daily data on JII's stock price and trading volume were analyzed using descriptive statistics, normality tests, Friedman Test, and Wilcoxon Signed Ranks Test. The results of the Friedman Test showed that the AR hypothesis was rejected, while the TVA was accepted, indicating that there was no significant difference in AR, but there was a significant difference in the TVA around the date of the event. The Wilcoxon Signed Ranks Test shows a rejection of the AR hypothesis on all events and the TVA only shows significant differences in the events of the Presidential and Vice President's Inaugurations.